1) 6(a-2)(a-3)-4(a-3)²=6(a²-5a+6)-4(a²-6a+9)=6a²-30a+36-4a²+24a-36=2a²-6a
2) (2x²+x-5)²-(2x²+x)(2x²+x-1)+9(2x²+?)=?
3) (m²+n-4)²-(m²+n-1)(m²+n-8)=m⁴+2m²(n-4)+(n-4)²-m⁴-m²n+8m²-m²n-n²+8n+m²+n-8=
=m⁴+2m²n-8m²+n²-8n+16-m⁴-m²n+8m²-m²n-n²+8n+m²+n-8=
=m²+n+8
1) 6(a-2)(a-3)-4(a-3)²=6(a²-5a+6)-4(a²-6a+9)=6a²-30a+36-4a²+24a-36=2a²-6a
2) (2x²+x-5)²-(2x²+x)(2x²+x-1)+9(2x²+?)=?
3) (m²+n-4)²-(m²+n-1)(m²+n-8)=m⁴+2m²(n-4)+(n-4)²-m⁴-m²n+8m²-m²n-n²+8n+m²+n-8=
=m⁴+2m²n-8m²+n²-8n+16-m⁴-m²n+8m²-m²n-n²+8n+m²+n-8=
=m²+n+8